The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/ors.12323
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous mandibular xanthomas – an interesting diagnostic dilemma?

Abstract: Intraosseous xanthomas are rare, benign entities and may present a diagnostic challenge to clinicians, radiologists and histopathologists due to the non‐specific features of this lesion. Presented here is the first definitive reported recurrence of an intraosseous xanthoma, which was previously diagnosed as a granular cell odontogenic tumour. We include a review of the existing literature and discuss the diagnostic pitfalls in navigating the differences between granular cell odontogenic tumour and intraosseous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Glycaemia levels were reported in five studies and lipidemia levels in 12, being within normal limits in all cases. Only one study demonstrated a case of IOX of the jaws with hyperlipidaemia.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Glycaemia levels were reported in five studies and lipidemia levels in 12, being within normal limits in all cases. Only one study demonstrated a case of IOX of the jaws with hyperlipidaemia.…”
Section: Resultsmentioning
confidence: 77%
“…After the elimination of 192 duplicates, the parameters for inclusion and exclusion were applied to 442 references. A total of 16 articles reporting 31 cases of IOX of the jaws were selected . The studies included in the present literature review were case reports or case series.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations